2021
DOI: 10.5194/acp-21-18319-2021
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde evolution in US wildfire plumes during the Fire Influence on Regional to Global Environments and Air Quality experiment (FIREX-AQ)

Abstract: Abstract. Formaldehyde (HCHO) is one of the most abundant non-methane volatile organic compounds (VOCs) emitted by fires. HCHO also undergoes chemical production and loss as a fire plume ages, and it can be an important oxidant precursor. In this study, we disentangle the processes controlling HCHO by examining its evolution in wildfire plumes sampled by the NASA DC-8 during the Fire Influence on Regional to Global Environments and Air Quality experiment (FIREX-AQ) field campaign. In 9 of the 12 analyzed plume… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 59 publications
3
30
0
Order By: Relevance
“…Chemical age can be estimated based on known differential reaction rates of species, or the physical age can be estimated. Here we estimate the physical age based on air mass trajectories comprising two components: advection age and plume rise age (Liao et al, 2021). The advection time was estimated by the HYbrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT; Rolph et al, 2017;Stein et al, 2015) from the DC-8 aircraft location relative to the smoke source identified using the MODIS-/ASTER airborne simulator (MASTER; Hook et al, 2001) with multiple high-resolution meteorological datasets, including High-Resolution Rapid Refresh (HRRR), the North American Mesoscale Forecast System (NAM CONUS nest) and the Global Forecast System (GFS).…”
Section: Age Of Smoke Plumesmentioning
confidence: 99%
“…Chemical age can be estimated based on known differential reaction rates of species, or the physical age can be estimated. Here we estimate the physical age based on air mass trajectories comprising two components: advection age and plume rise age (Liao et al, 2021). The advection time was estimated by the HYbrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT; Rolph et al, 2017;Stein et al, 2015) from the DC-8 aircraft location relative to the smoke source identified using the MODIS-/ASTER airborne simulator (MASTER; Hook et al, 2001) with multiple high-resolution meteorological datasets, including High-Resolution Rapid Refresh (HRRR), the North American Mesoscale Forecast System (NAM CONUS nest) and the Global Forecast System (GFS).…”
Section: Age Of Smoke Plumesmentioning
confidence: 99%
“…Chemical age can be estimated based on known differential reaction rates of species, or the physical age can be estimated. Here we estimate the physical age based on air mass trajectories comprising two components: advection age and plume rise age (Liao et al, 2021). The advection time was estimated by the HYbrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT; (Rolph et al, 2017;Stein et al, 2015))…”
Section: Age Of Smoke Plumesmentioning
confidence: 99%
“…4-nitrophenol, 4-nitrocatechol, and their derivatives are now commonly identified BrC species (Bluvshtein et al, 2017;Hems and Abbatt, 2018); other identified chromophores include a range of polycyclic aromatic hydrocarbons (PAHs) derivatives and polyphenols that span wide molecular weights and structures (Lin et al, 2016). Carbonyl functional groups are a common feature of BrC chromophores (Laskin et al, 2015;Lin et al, 2015a;De Haan et al, 2017). Evidence suggests that strongly absorbing chromophores comprise a small mass fraction of OA in biomass burning smoke, but dominate the overall BrC absorption (Nguyen et al, 2012;Laskin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plume ages for each transect were calculated using back trajectory analysis (Liao et al., 2021). Fire source locations were identified based on point of ignition reported by the National Interagency Fire Center, and confirmed with MODIS and VIIRS satellite detections.…”
Section: Experimental Approachmentioning
confidence: 99%